Plantio direto e plantas de cobertura afetam as propriedades químicas do solo e desempenho agronômico do milho - Fabio Lima Abrantes (2024)
The proper soil management associated with cover crops is of fundamental importance in agricultural practices to ensure the good development of the crop and promote increases in productivity. The objective was to evaluate the influence of different soil management systems and cover crops on the production components and productivity of corn, as well as on the soil's chemical properties. The experiment was conducted in a 3 x 3 factorial scheme, with three soil preparation systems (Minimum Tillage System - SCM, Conventional Tillage System - SPC, and No-Tillage System - SPD) and three cover crops (Urochloa ruziziensis "brachiaria", Forage Turnip, and Crotalaria spectabilis). Soil preparation took place in March 2022, cover crops were sown in September 2022, cover crops were desiccated in January 2023, and hybrid corn AS 1820 PRO3 was sown in February. The production components and grain yield of corn were measured, and after the harvest, soil samples were collected to evaluate the soil's chemical composition. The no-tillage system improves the ear insertion height, final plant height, ear diameter, and corn productivity. Brachiaria favors final plant height and number of grain rows. The no-tillage system provides favorable conditions for plant development, and crotalaria and brachiaria responded better as cover crops. The organic matter (OM) and organic carbon (OC) content in the soil were influenced by the interaction of management systems and cover crops, with crotalaria followed by brachiaria in no-tillage system being the covers that favor an increase in OM and OC. Turnip in no-tillage system does not contribute positively to increasing OM and OC. The cation exchange capacity in the soil was lower in no-tillage system. There is variation in soil pH due to the interaction of management systems and cover crops. In conventional tillage system, crotalaria and brachiaria cover crops were conditions where increases in soil phosphorus content were obtained. The potassium content is favored by brachiaria cover crop, while manganese is favored by crotalaria followed by brachiaria; copper (Cu) content is higher in SCM followed by SPC, and iron (Fe) content is higher in SPD followed by SCM. It is concluded that the no-tillage system promoted the best result in corn productivity, with brachiaria being the best cover crop in this system. Cover crops depend on the adopted soil management. Keywords: Soil preparation. Productivity. Minimum tillage system. Conventional tillage system. No-tillage systems.